Pengaruh Kesadaran Wajib Pajak, Kewajiban Moral, Tingkat Pendidikan dan Kondisi Keuangan pada Kepatuhan Wajib Pajak Kendaraan Bermotor - Kadek Ayu Widia; I Nyoman Putra Yasa (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
The objective of this present study is to use the variable awereness of taxpayers, moral obligations, education level and financial condition of taxpayer compliance. This study was carried out at the Joint Office of Samsat Karangasem Regency. Population of this study is the taxpayer of two-wheeled motor vehicles registered at the Joint Office of Samsat Karangasem Regency, amounting to 327,256 units. The method of determining the sample is the accidental sampling method and obtained a total sample of 348 respondents. The questionnaire is filled via online, particularly with google form to avoid the danger of Covid-19. Data that has been collected is then tested in advance with descriptive ststisticsl tests, test instruments, test classic assumptions, and proceed with hypothesis testing Quantitative analysis techniques applied in this study are multiple regression techniques. Other hypothesis tests are t test and R2 with SPSS version 21 for windows. Findings of this study indicated taxpayer compliance is influenced by several variables including taxpayer awareness (X1), moral obligation (X2), education level (X3), financial condition (X4) positively and significantly.